Formation of intermetallic δ phase in Al-10Si-0.3Fe alloy investigated by in-situ 4D X-ray synchrotron tomography. (1st May 2017) - Yu, J.M.; Wanderka, N.; Rack, A.; Daudin, R.; Boller, E.; Markötter, H.; Manzoni, A.; Vogel, F.; Arlt, T.; Manke, I.; Banhart, J.
Abstract: During solidification of Fe-containing Al-Si casting alloys, various different intermetallic phases are formed. As this can have an impact on mechanical properties we investigated phase formation by applying in-situ time resolved synchrotron X-ray tomography. For a commercially pure Al-10Si-0.3 wt.% Fe alloy, phase morphology and spatial arrangement during solidification was revealed with 1 °C temperature resolution. We find that many of the intermetallic phases that have been identified as β-AlFeSi phases in previous studies are in fact δ phases. It was found that δ plates mainly nucleate on the eutectic Al and Si. δ phase formation terminates almost simultaneously with the final solidification of eutectic phases. Features of δ phase growth such as impingement, branching and deformation of plates are discussed. The phase separation sequence during solidification is described and explained by the existence of "cells" of residual liquid in which δ phase formation progresses rapidly due to the supersaturation of solute atoms. Graphical abstract: Image